Optimal weighting on assessed subject areas of saber 11 test to compute the admission score (Revista de Investigaciones Universidad del Quindío, 2015)
SABER11 are standardized tests used by many Colombian universities as a selection tool to admit fi rstyear students at different academic programs. The total score for each applicant is generally calculated by a weighting scheme where a different weight is applied to each area in standardized test. These weights are chosen according to the academic program that the prospective student is applying to. This paper presents a method to calculate optimally the weights for each area in the SABER11 tests according to the academic program. The proposed method is based on the assumption that the admission score should be related to subsequent students academic performance. A validation with real data is also illustrated.
Keywords: Correlation Matrix; Lagrange Multipliers; optimal weighting; SABER11 standardized test